THE IMPACT OF THE EXPLOITING ACTIVITIES OF ORES ON WATER QUALITY AND DEPOLLUTING METHODS OF THE MINEWATERS - Daniela CÎRŢÎNĂ; Irina PECINGINĂ (Fiabilitate şi Durabilitate, 2013)
In the case of mine works, the waters coming from underground which are discharged in emissariesare charged with harmful substances. This situation imposes additional depolluting measures of these watersbefore the discharge, for reaching to the maximum admissible contents. The paper analysis the negative effectsof the extracting activity of ores on the water quality and presents the depolluting methods which should beapplied in order to reduce the concentration of harmful substances present in the mine waters